Elaboração de massa de pastel sem glúten - Veiga, André Moro (2014)
Pasta or macaroniare unfermented product, presented in various forms obtained by mechanical mixing of the flour or wheat semolina with cold or warm water. Gluten is a complex of 75 % protein, 15% carbohydrates, 6 % fat and 0.8 % minerals. The gluten proteins account for 80 % of total proteins in wheat and fall into two classes, gliadins, which belong to the class of glutenin and prolamine. This work prepared the pastry dough gluten free, making 2 formulations until a mass close to traditional features. We analyzed the water activity, and color of both formulations. Realized that the masses had similar values, but to formulate 2 although there was a small difference in the color analysis on coordinate L *, which indicates brightness pointing a lighter mass formulation 1. The first result was the formulation of a rather brittle and after frying batter, quite rigid texture. In the second attempt with the addition of some ingredients, has come up with a final product appearance and texture very similar to traditional pastel.